Active political engagement, political patronage, and local labour markets - the example of Shkoder - Elvisa Drishti; Bresena Kopliku; Drini Imami (Global Labor Organization (GLO), 2022)
Purpose: This paper aims to contribute to understanding of the effects of active political engagement in port-of-entry jobs and employment pathways for graduate students. The data are derived from a structured survey of a small local labour market where political clientelism is pronounced due to the strong network ties. Controlling for both demand and supply factors we identify a profile for those who are more prone to engage politically in exchange for public sector jobs, which are in turn vulnerable to regime changes. Design/methodology/approach: We use data from a sample of 191 participants that records month-tomonth employment states for three consecutive years (2012-2014). The method attempts to replicate an experimental design with repeated measures before and after the June 2013 government elections. The data is analysed using sequence analysis with optimal matching and difference-in-difference methods. Note: This is the final submitted version of the manuscript accepted for publication by the International Journal of Manpower, on the 5th of February 2022. Findings: The analysis provides evidence of links between political engagement and selection onto different employment pathways. The pathways themselves are also shown to be differentially impacted by the 2013 election (positively or negatively). Together, these results are supportive of claims that jobs in Albania, particularly those in the public sector, are linked to the short-term presence of vote-buying and the political business cycle. This is shown to be the case even for this sample of educated members of the labour force (i.e. university graduates). The analysis also finds evidence of accumulative disadvantages over time, in relation to subjective perceptions of life satisfaction, migration intentions, employability and success in life, as a result of active political engagement. Originality: The study uses a unique data set and a novel methodology, sequence analysis. Occupational history calendars were used to capture quantitative information recording detailed work histories. To the best of our knowledge, this innovative method has not been used before to measure the temporal effects of political engagement on employment pathways.
Additional information: This is the final submitted version of the manuscript accepted for publication by the International Journal of Manpower, on the 5th of February 2022.
Keywords: 330; political clientelism; Albania; higher education; sequence analysis; employment pathways